Screening, design, synthesis and bioactivity of inhibitors against Protein Arginine Deiminase type IV - Teo, Chian Ying (2015)
Protein Arginine Deiminase IV (PAD4) is a new target for rheumatoid arthritis (RA) therapeutic. It catalyses the citrullination process in human body that produces citrullinated protein which is believed to be the root cause of RA. Inhibitor for the enzyme can be a drug for the treatment of RA. The main objective of this research is to search for potent inhibitors for PAD4. Human PAD4 has been successfully expressed in Escherichia coli BL21 (DE3). PAD4 expressed from pET32b vector with the use of auto-induction media introduced by Studier gave higher solubility and activity compared to conventional induction system. PAD4 was successfully purified using affinity chromatography technique with purity of 90%, approximately. Several compounds have been identified as potential inhibitors for PAD4 by structure-based virtual screening using Ligand Discovery at Edinburgh University (LIDAEUS) programme. Three compounds out from 22 top-ranked water-soluble compounds showed significant inhibition to PAD4 and their IC50 values were ranged from 1.49 ± 0.03 to 2.96 ± 0.01 mM. Binding affinities of the compounds to PAD4 obtained from molecular docking were -7.49, -7.27 and -6.00 kcal/mol. The structures of the three compounds showed no resemblance with previously discovered PAD4 inhibitors, nor with existing drugs for RA treatment. Ultrafast Shape Recognition (USR) was utilized in searching of compounds possess similar molecular shape with previous reported inhibitor, streptonigrin. Five compounds out of the selected 37 compounds inhibited enzymatic activity of PAD4 significantly, with more than 10% inhibition at 100 μM. The best compound, (2E)-N-{(2R)-1-[(furan-2-ylmethyl)(methyl)amino]-1-oxopropan-2-yl}-3-(4-methoxyphenyl) prop-2-enamide, is a moderate inhibitor for PAD4 with IC50 value of 362.67 ± 4.13 μM. The structure of the compound showed no resemblance with the parent compound. Interestingly, furan ring in USR discovered compound was able to enter the active site cleft of PAD4. Four peptide-based inhibitors incorporated with non-standard amino acid containing furan ring (X) with sequence based-on PAD4 natural substrate, nucleophosmin were designed and synthesized using solid phase technique. Circular dichroism spectroscopy showed that the structure of the designed peptide-based inhibitors was predominantly unordered. The IC50 value of the best peptide-based inhibitors with sequence KSIXDTP is 243.2 ± 2.4 μM which is lower than compounds obtained from LIDAEUS and USR. Kinetic studies revealed that it inhibited PAD4 reversibly and competitively. Three dimensional structure of the best peptide-based inhibitor was further elucidated using nuclear magnetic resonance spectroscopy. Molecular docking of the peptide-based inhibitor suggested favourable interaction between the peptide with PAD4 with binding affinity of -5.4 kcal/mol. Inhibitors containing furan ring in the structure show high potential in inhibiting PAD4 and the structure of the inhibitors discovered in this research can be modified to be a better drug candidate for treatment of rheumatoid arthritis.